Becoming dehumanized by a service robot: An empirical examination of what happens when non-humans perceive us as less than full humans - Söderlund, Magnus (Computers in Human Behavior: Artificial Humans, 2025)
Service robots are expected to become increasingly common, and one fundamental task for them is to detect when a human user is present. Thus, they need to be able to correctly categorize a user as a “user”. So far, however, little is known about how users react to robots' understanding of what a user is in terms of a superordinate social category, namely “human”. Given that we humans are sensitive to how we are categorized by others, particularly when we are dehumanized in the categorization process, it was assumed in the present study that this sensitivity may materialize also when the categorizer is a (humanlike) service robot. This assumption was examined with two between-subjects experiments in which a service robot's categorization of the user was manipulated (low vs. high dehumanization). The main finding was that high robotic dehumanization had a negative impact on the user's overall evaluation of the robot.